(untitled) (UNIZIK Journal of Educational Management and Policy, 2024)
The study investigated the social and economic management strategies for ensuring quality assurance in public secondary schools in Anambra State. Two research questions guided the study and two hypotheses were tested. The descriptive survey research design was adopted for the study and the population of the study comprised 263 public secondary school principals. The instrument for data collection was a structured validated questionnaire which was subject to a pilot test. Data collected from the pilot test was analysed using Cronbach Alpha. The analysis yielded coefficient values of 0.86 for cluster 1 and 0.82 for cluster 2. The overall reliability coefficient value for the entire questionnaire was determined to be 0.84. Mean, standard deviations and t-test were used to analyze data for the study. Findings of the study revealed that encouraging open and effective communication between teachers, students, parents, and other personnel as well as creating a positive school culture that values respect are some of the social management strategies for ensuring quality assurance in public secondary schools in Anambra State. Findings also revealed that ensuring that funding are allocated to areas that have a direct impact on teaching and learning, establishing scholarship programmes to support financially disadvantaged but academically gifted students, actively seeking external funding sources, such as grants and donations, to supplement the school’s budget are some of the economic management strategies for ensuring quality assurance in public secondary schools in Anambra State. The gender of the respondents did not influence their opinions. Based on these findings, the researchers recommended among others that Principals should prioritise and support open and effective communication among teachers, students, parents, and school workers